Application of Fluorescent In Situ Hybridization for Quick Identification of Microorganisms from Positive Blood Cultures - Lengerova, Gergana; Kalchev , Yordan; Rachkovska, Zoya; Raycheva , Ralitsa; Petrov, Michael; Murdjeva, Marianna (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study was to evaluate the diagnostic potential of the fluorescent in situ hybridization (FISH) method for quick identification of microorganisms from positive blood cultures. MATERIALS AND METHODS: QuickFISH BC is a multicolor, qualitative nucleic acid hybridization assay using specific fluorescent-labeled probes for identification of Gram-positive bacteria (S. aureus, Coagulase-negative Staphylococcus spp. – CoNS, E. faecalis, and E. faecium); Gram-negative bacteria (E. coli, P. aeruginosa, and K. pneumoniaе), and fungi (C. albicans, C. tropicalis, and C. glabrata). This method applied to 72 positive blood cultures obtained from patients admitted at the University Hospital St. George – Plovdiv. A preliminary selection based on Gram staining was performed before the application of the FISH test. All microorganisms were subject to identification by routine biochemical tests, semi-automated and automated systems as well. Statistical data processing included descriptive statistics, nonparametric analysis for testing hypotheses by SPSS v. 22.0, and Microsoft Excel software. p < 0.05 was considered statistically significant. RESULTS: FISH detected microorganisms in 63 (87.5%) positive blood cultures, whereas no fluorescent signal was observed in 9 (12.5%). The latter was because not all the microorganisms we identified are included in the test spectrum, for example – Enterobacter spp. and Acinetobacter spp. By FISH, we found S. aureus in 10 (15.9%) cases, CoNS in 20 (31.6%), E. faecalis in 4 (6.4%), and E. faecium in 4 (6.4%). E. coli (n = 7; 11.1%) was the leading cause of bacteremia among Gram-negative bacteria, whereas C. albicans predominated (n = 4; 6.4%) among fungi. CONCLUSION: QuickFISH BC is a rapid and accurate screening method for the identification of some of the most frequent pathogens causing bacteremia. This enables the initiation of the early and adequate antimicrobial therapy. The lack of pathogen identification from positive blood cultures using this method implies the need to continue identification with other tests.